030 Emerging parkinsonism in the PREDICT-PD cohort after 5-year follow-up. Issue 6 (27th May 2022) - Simonet, Cristina; Bestwick, Jonathan; Schrag, Anette; Lees, Andrew; Noyce, Alastair
Abstract : Background: The PREDICT-PD study is a web-based study which aims to identify individuals aged 60–80 at risk of future Parkinson's disease (PD) from the UK general population. Soon after enrolment, representative groups of individuals that were classified as higher risk (HR) or lower risk (LR) (highest and lowest 15% of risks scores) were reviewed 'in person' with HR group being more likely to show subtle motor impairment compared with the LR group. Methods: Individuals were examined using the motor part of Unified PD Rating Scale (MDS-UPDRS-III) after a minimum of 5-year follow-up. Findings: We reviewed 132 participants (HR:33, LR:99). HR subjects were predominantly male (74.2%) and older (77.2yo vs 73.6yo, p<0.001). At 5-year follow-up a bigger change in MDS-UPDRS-III was seen amongst HR individuals compared to LR group (36% vs 13% increasing > 5 points in the motor scale). In contrast to the baseline analysis, where there were no significant differences on a keyboard tapping test (BRAIN test), HR participants performed worse than LR participants (43.7key/sec vs 53.9key/sec, p<0.001) after 5 years. Two participants received a PD diagnosis during follow-up with respective motor signs demonstrated 2 and 5 years before fulfilling clinical diagnosis criteria. Conclusions: This study identifies early motor features and their evolution during PD pre-diagnostic phase. Remotely administered tools may be capable of detecting subtle motor dysfunction at early stages of PD. c.simonet@qmul.ac.uk|NIHR Bursary 40